Temperature and Impedance Variations During Tumor Treating Fields (TTFields) Treatment - Gentilal, Nichal; Abend, Eyal; Naveh, Ariel; Marciano, Tal; Balin, Igal; Telepinsky, Yevgeniy; Miranda, Pedro Cavaleiro (Frontiers in Human Neuroscience, 2022)
Tumor Treating Fields (TTFields) is an FDA-approved cancer treatment technique used for glioblastoma multiforme (GBM). It consists in the application of alternating (100–500 kHz) and low-intensity (1–3 V/cm) electric fields (EFs) to interfere with the mitotic process of tumoral cells. In patients, these fields are applied via transducer arrays strategically positioned on the scalp using the NovoTAL™ system. It is recommended that the patient stays under the application of these fields for as long as possible. Inevitably, the temperature of the scalp increases because of the Joule effect, and it will remain above basal values for most part of the day. Furthermore, it is also known that the impedance of the head changes throughout treatment and that it might also play a role in the temperature variations. The goals of this work were to investigate how to realistically account for these increases and to quantify their impact in the choice of optimal arrays positions using a realistic head model with arrays positions obtained through NovoTAL™. We also studied the impedance variations based on the log files of patients who participated in the EF-14 clinical trial. Our computational results indicated that the layouts in which the arrays were very close to each other led to the appearance of a temperature hotspot that limited how much current could be injected which could consequently reduce treatment efficacy. Based on these data, we suggest that the arrays should be placed at least 1 cm apart from each other. The analysis of the impedance showed that the variations seen during treatment could be explained by three main factors: slow and long-term variations, array placement, and circadian rhythm. Our work indicates that both the temperature and impedance variations should be accounted for to improve the accuracy of computational results when investigating TTFields.